Peran Reverse Logistic Dalam Meningkatkan Efisiensi Dan Efektivitas Perusahaan Dalam Rantai Pasokan Studi Kasus: Pt. Graha Auto Perkasa - Immanuel Zai; Figo Winnerko; Andrian, William, Hardi Suandri, Delvian Yosuky, Vincent Linardo (Jurnal Mirai Management, 2023)
Reverse logistics is a concept related to the management of the flow of goods or products, including the application process, control, and planning of raw materials, finished goods, and inventory within the supply chain. This article explains how reverse logistics operates in the company PT. Graha Auto Perkasa, outlining several stages of the cycle that must be traversed. The analysis technique used involves interviews with relevant individuals within the company PT. Graha Auto Perkasa. In this analysis, it is recommended that the company utilize the suggested reverse logistics cycle process to make the reverse logistics process more efficient and effective in the supply chain of PT. Graha Auto Perkasa. Keywords: reverse logistics, cycle, efficient, effective